Los efectos de los potenciales moleculares en la ecuación de estado de un gas real - Mauricio García Castañeda (Momento, 1992)
After a short discussion about the real origin of the Van der Walls equation as well the physical basis of its coefficients, using a simple model, we analize the effects on the Van der Walls constants when the values of the molecular potential parameters are modified.